Pengembangan Video Stopmotion Eksplorasi Etnomatematika Cerita Rakyat Legenda Roro Jonggrang Pada Pembelajaran Matematika - Adib Rozan; Bayu Aji; Hizbulloh Khalil Al Jamil; Abdul Karim (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to develop a stopmotion video of ethnomathematical exploration based on the folklore of the Roro Jonggrang legend in mathematics learning. The method used involves collecting data from relevant ethnomathematical sources and analyzing the content of folklore to find mathematical elements that can be used in learning. The results of the study show that the folklore of the Roro Jonggrang legend can be used as an effective medium in developing students' mathematical abilities through the use of mathematical elements contained in the story. The stopmotion videos made can help students understand mathematical concepts in a more fun and interactive way. This research is expected to contribute to the development of mathematics learning that is more innovative and relevant to local culture.